Efficacy of Uterine Artery Doppler Changes, Platelet Indices and Combination of Both in Prediction of Preeclampsia in Pregnant Women: A Prospective Observational Study - Firdous Fatima; Sangeeta Shah; Disha Shah; Mrinalini Mitra; Tummala Nishitha (International Journal of Anatomy Radiology and Surgery)
Introduction: Preeclampsia is a pregnancy-specific medical disorder characterised by an abnormal vascular response to placentation. Uterine artery Doppler ultrasound has emerged as a predictive tool in preeclampsia. Abnormal Doppler waveforms have been associated with impaired placental perfusion and an increased risk of developing preeclampsia. Preeclampsia is associated with alterations in platelet function and activation. The estimation of platelet indices is an easy and economical method for screening preeclampsia. Abnormal uterine artery Doppler findings and abnormal platelet indices are both related to the etiological pathways of preeclampsia. Aim: To compare the efficacy of uterine artery Doppler changes, platelet indices alone and their combination in predicting preeclampsia among pregnant women. Materials and Methods: This was a prospective observational study conducted Department of Obstetrics and Gynaecology, Gandhi Hospital in Secunderabad, Telangana, India, over 18 months, including 160 pregnant women aged 18-35 years with singleton pregnancies between 20-24 weeks of gestational age. Doppler ultrasound and platelet indices were measured and patients were followed-up until delivery for the development of preeclampsia. Receiver Operating Characteristic (ROC) curves were constructed and sensitivity, specificity and accuracy were determined to predict preeclampsia. Results: The mean age of the study population was 25.9±4.04 years. The sensitivity, specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV) and accuracy of platelet indices in predicting preeclampsia alone were 67.71%, 59.38%, 71.43%, 55.07% and 64.38%, respectively. The sensitivity, specificity, PPV, NPV and accuracy of the uterine artery Doppler indices in predicting preeclampsia alone were 77.08%, 68.75%, 78.72%, 66.67% and 73.75%. The combined assessment of uterine artery Doppler study and platelet indices in the prognostication of preeclampsia had a sensitivity of 85.42%, specificity of 82.81%, PPV of 88.17% and NPV of 79.10%, with improved accuracy of 84.38%. Conclusion: A combination of uterine artery Doppler ultrasound with platelet indices is easy to use, affordable, readily available in clinical settings and more effective in predicting preeclampsia than when used individually.